2020
DOI: 10.1080/15538362.2020.1774476
|View full text |Cite
|
Sign up to set email alerts
|

Role of Maturity Stages on Phenolic Compounds and Organic Acids Contents in Red Currant Fruits

Abstract: The aim of this research was to determine the changes in the organic acids and phenolic compounds in fruits of red currant due to maturity. It was harvested two cultivars (Red Lake and Rovada cv.) during four different maturity stages (green color, veraison, pink color, and red color) in red currant orchard in Bolu province. In red currant fruits 12 phenolic compounds (gallic acid, protocatechuic acid, catechin, chlorogenic acid, vanillic acid, syringic acid, p-coumaric acid, ferulic acid, o-coumaric, rutin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
3
16
1
Order By: Relevance
“…Early-ripening cultivars had higher values of vitamin C compared to mediumand late-ripening cultivars. Berk et al (2020) recorded that the content of vitamin C varied depending on the ripening stages. Redalen (1993) found that the ascorbic acid content of black currants is reduced by elevated temperature.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Early-ripening cultivars had higher values of vitamin C compared to mediumand late-ripening cultivars. Berk et al (2020) recorded that the content of vitamin C varied depending on the ripening stages. Redalen (1993) found that the ascorbic acid content of black currants is reduced by elevated temperature.…”
Section: 4mentioning
confidence: 99%
“…Moreover, the fruits, leaves and seeds of currants contain certain phenolic compounds, such as anthocyanins, catechins, proanthocyanidins, flavonols and hydroxycinnamic acids and other non-coloured flavonoids (Djordjevic et al, 2010;Šavikin et al, 2013;Mikulic-Petkovsek et al, 2016), which make them an interesting target for the functional food industry. The anthocyanins are water-soluble pigments and their content in currants depends on several factors, such as weather during the growing season, harvesting time and fruit maturity, but mostly on the genetic predisposition (Stanus et al, 2019;Berk et al, 2020). The most frequently occurring anthocyanidin in red currant berries is cyanidin, and the common sugars bonded to anthocyanidins are glucose, xylose and rhamnose (Veberič et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The main anthocyanins identified in red currant are cyanidin-3- O -rutinoside, cyanidin-3- O -xylosylrutinoside and cyanidin-3- O -glucoside [ 9 , 10 ]. Also, vitamin C content is relatively low compared to that of black currant, whereas the content in the range from 20 to 70 mg/100 g is still appreciable from the nutritional point of view [ 2 , 7 , 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reported 68 µg/g d.w. gallic acid for bilberries, 830 µg/g d.w. caffeic acid for bilberries and 56 µg/g d.w. for sea buckthorns, ferulic acid 148 µg/g d.w. for bilberries and 48 µg/g d.w. for sea buckthorns and quercetin 439 µg/g d.w. for bilberries and 212 µg/g d.w. for sea buckthorns [ 61 ]. Berk et al (2020) analyzed red currantssssss from Turkey and found gallic acid 8.05 µg/g d.w., catechin 132.75 µg/g d.w., syringica acid 5.15 µg/g d.w., ferulic acid 13.95 µg/g d.w., rutin 99.30 µg/g d.w. and quercetin 6.30 µg/g d.w. [ 62 ].…”
Section: Resultsmentioning
confidence: 99%